Climate limits vegetation green-up more than slope, soil erodibility, and immediate precipitation following high-severity wildfire - Crockett, Joseph L.; Hurteau, Matthew D. (Fire Ecology, 2024)
Background In the southwestern United States, post-fire vegetation recovery is increasingly variable in forest burned at high severity. Many factors, including temperature, drought, and erosion, can reduce post-fire vegetation recovery rates. Here, we examined how year-of-fire precipitation variability, topography, and soils influenced post-fire vegetation recovery in the southwestern United States as measured by greenness to determine whether erosion-related factors would have persistent effects in the longer post-fire period. We modeled relationships between post-fire vegetation and these predictors using random forest and examined changes in post-fire normalized burn ratio across fires in Arizona and New Mexico. We incorporated growing season climate to determine if year-of-fire effects were persistent during the subsequent 5 years or if temperature, water deficit, and precipitation in the years following fire were more influential for vegetation greenness. We expected that post-fire factors that drive erosion would reduce greenness; however, these effects would explain less variability in post-fire greenness than growing season climate. Results We found reductions in post-fire greenness in areas burned at high severity when heavy and intense precipitation fell on more erodible soils immediately post-fire. In highly erodible scenarios, when accounting for growing season climate, coefficient of variation for year-of-fire precipitation, total precipitation, and soil erodibility decreased greenness in the fifth year. However, more of the variation in greenness was explained by variability of growing season vapor pressure deficit and growing season precipitation. Conclusions Our results suggest that while the factors that contribute to post-fire erosion and its effects on vegetation recovery are important, at a regional scale, the majority of the variability in post-fire greenness in high-severity burned areas in southwestern forests is due to climatic drivers such as growing season precipitation and vapor pressure deficit. Given the increasing scale of area burned at high severity and the potential for more post-fire erosion, quantifying how these factors alter ecosystem development is central to understanding how different ecosystem types will be distributed across these landscapes with additional climate change.